2021
DOI: 10.3390/cancers13112648
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pre-Diagnostic Serum Bile Acids and Hepatocellular Carcinoma: The Singapore Chinese Health Study

Abstract: Hepatocellular carcinoma (HCC) is a commonly diagnosed malignancy with poor prognosis. Rising incidence of HCC may be due to rising prevalence of metabolic dysfunction-associated fatty liver disease, where altered bile acid metabolism may be implicated in HCC development. Thirty-five bile acids were quantified using ultra-performance liquid chromatography triple-quadrupole mass spectrometry assays in pre-diagnostic serum of 100 HCC cases and 100 matched controls from the Singapore Chinese Health Study. Conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
(72 reference statements)
4
23
0
Order By: Relevance
“…Conjugated primary BAs are significantly elevated at the stage of cirrhosis and continue to increase with the progression of HCC. 148 , 149 The role of BAs in the development of HCC is well-established and was extensively reviewed elsewhere. 150 Fundamentally, BAs activate farnesoid X receptor (FXR) and G-protein coupled BA receptor 1 (GPBAR1) that both control numerous oncogenic processes, including inflammation, oxidative stress, and the regulation of many cancer-related genes.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“…Conjugated primary BAs are significantly elevated at the stage of cirrhosis and continue to increase with the progression of HCC. 148 , 149 The role of BAs in the development of HCC is well-established and was extensively reviewed elsewhere. 150 Fundamentally, BAs activate farnesoid X receptor (FXR) and G-protein coupled BA receptor 1 (GPBAR1) that both control numerous oncogenic processes, including inflammation, oxidative stress, and the regulation of many cancer-related genes.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“…In another study from Taiwan, the Risk Evaluation of Viral Load Elevation and Associated Liver Disease/Cancer (REVEAL) cohort did not support the hypothesis that higher levels of secondary bile acids increase liver cancer risk; in fact, higher levels of the secondary bile acid deoxycholic acid were inversely associated with HCC [35]. This concept is compatible with a recent study from Singapore, in which the ratios of secondary bile acids over primary bile acids were associated with a decreased HCC risk [36]. The results of the present study demonstrate that HCC patients received cholecystectomy with a lower recurrence rate, rather than non-HCC patients receiving cholecystectomy with increasing rates of liver tumors.…”
Section: Discussionmentioning
confidence: 59%
“…However, the result of another study was that conjugated primary BAs were significantly elevated, whereas the ratios of secondary BAs over primary BAs were significantly lower in HCC cases than in controls (36). The doubling ratio of taurine-over glycine-conjugated CDCA was significantly associated with a 40% increased risk of HCC, whereas the doubling ratio of secondary over primary BAs was associated with a 30-40% reduced risk of HCC (36). In addition, a weighted relative difference accumulation algorithm study suggested that patients with hepatitis and cirrhosis had increased serum levels of G-CDCA, G-CA and T-CA and decreased serum levels of CDCA (37).…”
Section: Bas and Hccmentioning
confidence: 92%
“…A retrospective cohort study from 2004 to 2014 including 2,262 patients with chronic hepatitis B on conventional antiviral therapy indicated that persistent elevation of serum total BAs was an independent risk factor for HCC (35). However, the result of another study was that conjugated primary BAs were significantly elevated, whereas the ratios of secondary BAs over primary BAs were significantly lower in HCC cases than in controls (36). The doubling ratio of taurine-over glycine-conjugated CDCA was significantly associated with a 40% increased risk of HCC, whereas the doubling ratio of secondary over primary BAs was associated with a 30-40% reduced risk of HCC (36).…”
Section: Bas and Hccmentioning
confidence: 99%